Perspectives on Patient Experience: A National Survey of Hospitalists. (December 2020) - Khateeb, Rafina; Keniston, Angela; Moore, Amber; Hrach, Christine; Indovina, Kimberly A; Kneeland, Patrick; Rudolph, Mark; Burden, Marisha
Despite efforts to improve patient experience (PX), little is known about the perspective of hospitalists regarding PX initiatives and priorities. A survey was distributed to hospitalist groups across the country assessing involvement in PX initiatives and their perceived effectiveness, what PX means to providers, and facilitators/barriers in improving PX. Ninety-nine percent of respondents had encountered some improvement activity around PX. The most prevalent were communication training, group Hospital Consumer Assessment of Healthcare Providers and Systems data, and interdisciplinary bedside rounding. Respondents rated most initiatives a 5 to 6 out of 10 for their effectiveness, with the perception of effectiveness increasing with respondents' assessment of patient experience priority. Learning about others' experiences in improving PX and learning about potential collaborations for quality improvement or research in these areas were areas of interest for future work. Qualitative work highlighted potential barriers in improving PX such as workload and staffing constraints, uncontrollable environmental factors, and unrealistic patient expectations. Improving PX is a priority, and there are many initiatives in place with perceived variable success and perceived barriers in improving PX.